Simulations of tremor‐related creep reveal a weak crustal root of the San Andreas Fault. Issue 7 (13th April 2013) - Johnson, Kaj M.; Shelly, David R.; Bradley, Andrew M.
Abstract [1] Deep aseismic roots of faults play a critical role in transferring tectonic loads to shallower, brittle crustal faults that rupture in large earthquakes. Yet, until the recent discovery of deep tremor and creep, direct inference of the physical properties of lower‐crustal fault roots has remained elusive. Observations of tremor near Parkfield, CA provide the first evidence for present‐day localized slip on the deep extension of the San Andreas Fault and triggered transient creep events. We develop numerical simulations of fault slip to show that the spatiotemporal evolution of triggered tremor near Parkfield is consistent with triggered fault creep governed by laboratory‐derived friction laws between depths of 20–35 km on the fault. Simulated creep and observed tremor northwest of Parkfield nearly ceased for 20–30 days in response to small coseismic stress changes of order 104 Pa from the 2003 M6.5 San Simeon Earthquake. Simulated afterslip and observed tremor following the 2004 M6.0 Parkfield earthquake show a coseismically induced pulse of rapid creep and tremor lasting for 1 day followed by a longer 30 day period of sustained accelerated rates due to propagation of shallow afterslip into the lower crust. These creep responses require very low effective normal stress of 1 MPa on the deep San Andreas Fault and near‐neutral‐stability frictional properties expected for gabbroic lower‐crustal rock.